INFLUENCE OF LECTURER TRAINING ON THE PROFILE OF THE GRADUATE OF THE UNDERGRADUATE COURSE IN NURSING - Ana Paula Dias França Guareschi; Paulina Kurcgant (Universidade Federal do Paraná, 2014)
This study aims to investigate research undertaken in the area of nursing, which addresses the training of the nurse lecturer as an element which influences the construction of the profile of the nursing graduate. The method adopted was the integrative review, in the period 2007 - 2012, in the LILACS and Dedalus databases and in the SciELO text base. 24 articles were found, of which 14 were analyzed, meeting the study's inclusion criteria. Based on the profiles of the graduates of undergraduate nursing courses prevalent in the articles, the thematic analysis allowed the elaboration of the categories: Being an educator in the humanistic perspective; Being an educator in the construction of the critical/reflexive dimension and Being an educator with social responsibility. The articles evidence the need to reflect on the training of the nursing lecturer, this professional's essential characteristics and the influence which this training may have on the proposition of the profile of the nursing graduate.